Atlas petromineralogico of minerals and rocks of the Peru - Part I - Quiñones Lavado, Lourdes (2007)
The fundamental intention of this atlas is to illustrate, across the microscopic description of the rocks and minerals accompanied of its microphotographies, the range of the types of rocks and more signifi cant of the Peruvian territory and to demonstrate the form and the conditions of its formation, showed by its different textures and associations; likewise it will be done by the constituent minerals of the different types of deposits. mineral opposing species largely of the Deposits of Peru, is for this reason that the Laboratory of Optical Microscopy of the E.A.P. of Geological Engineering wants to present in a very special way this new atlas that will be of great utility for the community geological and been interested in the arts of the mineralogy. As for the rocks there have been born in mind its mineralogical composition, classifi cation and types of alterations (chemical, physical and meteoric), in samples from studies of exploration of deposits and of geotecnia. In case of the metallic minerals its description, alteration and texture has been born in mind. Likewise also it has been considered to be its relation by the environment, in this case considering to the generating minerals of pollutants.